(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Wind energy has now been utilized to propel sailboats and land-based windmill. In regard to commercial development, wind energy has become the most advanced among the renewable energy sources. This renewable source of energy is significant because it is easily accessible. The opportunity for expansion is vast, and Earth’s power significantly surpasses the worlds the need energy. A total from around 65000 Megawatt have been produced worldwide, with a yearly production of about 110 Terawatt-hour. Economics, land productivity, the atmosphere, and grid efficiency are the city development top priorities. In the last 26 years, the consumption of renewable energy has soared significantly. Since 2000, the growth rates for wind and solar remain stayed within the double digits. No other area of the energy sector has experienced this. Due to its cheap maintenance costs, lack of fuel costs, and development time of about a year as opposed to nuclear reactors’ 12 years, wind power has emerged as the most appealing new power plant technologies. Air pollution, greenhouse gases released from non-renewable renewable resources, prospective modifications in the production of renewable energy, and mining are just a few of the positive environmental consequences of wind power. A greater understanding of how a particular energy source wears down or is replaced by many other energy sources, as well as all other power sources that are available to the environment and the economy, is essential for a deeper comprehension of the environmental and economic consequences of any given energy source. The ecological impacts, both positive and negative are looked into in this research